2023
DOI: 10.1002/smll.202308783
|View full text |Cite
|
Sign up to set email alerts
|

Eu‐Based Porphyrin MOF Enables High‐Performance Carbon‐Based Perovskite Solar Cells

Dongqi Wu,
Huanyi Zhou,
Xiaoxia Lai
et al.

Abstract: The low power conversion efficiency (PCE) of hole transport materials (HTM) – free carbon‐based perovskite solar cells (C‐PSCs) poses a challenge. Here, a novel 2D Eu‐TCPP MOF (TCPP; [tetrakis (4‐carboxyphenyl) porphyrin]) sandwiched between the perovskite layer and the carbon electrode is used to realize an effective and stable HTM‐free C‐PSCs. Relying on the synergistic effect of both the metal‐free TCPP ligand with a unique absorption spectrum and hydrophobicity and the EuO4(OH)2 chain in the Eu‐TCPP MOF, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…37 Porphyrin, a type of porphin derivative with a large conjugated structure, is an excellent building block for HOF design and synthesis due to its rigid structure, tunable external substituents, and metallized ring center. 38–40 In particular, porphyrin molecules containing carboxyl groups have been extensively explored in the construction of various HOF structures based on tetrakis (4-carboxyphenyl) porphyrin (TCPP), 41 while research on dicarboxylphenyl porphyrin (DBP) remains scarce. Only a few metal–organic framework structures incorporating DBP ligands have been reported, such as alkaline earth metal-DBP-MOFs reported by Jiang et al , 3 DBP-UiO reported by Lin et al , 42–44 and Zn-DBP reported by Ma et al 45 DBP ligands are only supported on graphene, titanium dioxide, and other materials applied to catalysis that do not involve the single crystal structure of DBP.…”
Section: Introductionmentioning
confidence: 99%
“…37 Porphyrin, a type of porphin derivative with a large conjugated structure, is an excellent building block for HOF design and synthesis due to its rigid structure, tunable external substituents, and metallized ring center. 38–40 In particular, porphyrin molecules containing carboxyl groups have been extensively explored in the construction of various HOF structures based on tetrakis (4-carboxyphenyl) porphyrin (TCPP), 41 while research on dicarboxylphenyl porphyrin (DBP) remains scarce. Only a few metal–organic framework structures incorporating DBP ligands have been reported, such as alkaline earth metal-DBP-MOFs reported by Jiang et al , 3 DBP-UiO reported by Lin et al , 42–44 and Zn-DBP reported by Ma et al 45 DBP ligands are only supported on graphene, titanium dioxide, and other materials applied to catalysis that do not involve the single crystal structure of DBP.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it involves a non‐resonant excitation energy transfer, implying strong electron–phonon coupling of the carriers constituting the exciton, as opposed to the dipole‐dipole coupling in FRET processes. Chen et al [ 16 ] highlighted the absorption spectrum of perovskites overlaps with the PL spectrum of Eu‐TCPP MOF, suggesting the possibility of FRET between Eu‐TCPP MOF and perovskite layers. Similarly, Tan et al [ 17 ] underscored that MOFs serve as excellent platforms for triggering FRET mechanisms.…”
Section: Introductionmentioning
confidence: 99%